UPAYA PENINGKATAN PRESTASI BELAJAR PKn MELALUI METODE BERMAIN PERAN PADA SISWA KELAS IV SD NEGERI NOGOSAREN GAMPING SLEMAN - Nadziroh Nadziroh (Universitas Muhammadiyah Mataram, 2015)
This study is intended to increase the student’s achievement and process to excute the social studies learning withRole Playing approach.This study is a Classroom Action Research (CAR) implemented to 4th elementary students inSDN Nogosaren Gamping Sleman as the object of study. This study contains two cycles, starts from planning,implementation, monitoring, reflecting and improving. The data were collected by using learning achievement test,observations, and interviews. The data from learning achievement tests were analyzed by using the descriptivequantitative technique. The data from observations and interviews were analyzed by using the descriptive qualitativetechnique on the basics of the results of the observation and reflection.Findings suggest that by the Role Playingapproach implementation, the civic education can get its best result. The student’s score increases. It is proved bythe average score in each examination. At the first cycle, the average score is 69,43 and the second cycle is 74,90.